Human development : a life-span view - Kail, Robert V.; Cavanaugh, John C. (Belmont, California : Wadsworth Cengage Learning, 2010)
Offers coverage of the entire life span. This book presents a modified chronological approach that traces development in sequential order from conception through late life.
1. The study of human development -- 2. Biological foundations -- 3. Tools for exploring the world -- 4. The emergence of thought and language -- 5. Entering the social world -- 6. Off to school -- 7. Expanding social horizons -- 8. Rite of passage -- 9. Moving into the adult social world -- 10. Becoming adult -- 11. Being with others -- 12. Work and leisure -- 13. Making it in midlife -- 14. The personal context of later life -- 15. Social aspects of later life -- 16. The final passage
Includes bibliographical references (p. 643-742) and indexes
Keywords: Developmental psychology